Les reines mérovingiennes ont-elles une politique territoriale? - Santinelli, Emmanuelle (Revue du Nord, 2003)
Abstract: „If power rests in the Higher Middle Ages first on the control of riches and men, this does not exclude a perception of space. This paper raises the question of the policies led, so as to control and master the territories and the borders, by the Merlovingian queens who held a large share of the authority in the VIth–VIIth centuries (Clotilde, Brunehilde, Frédégonde, Nanthilde, Bathilde). It reveals their intervention in certain successions, privileging sharing or unity, according to the context, the way they manage to spread all over the kingdom bases of operation and relay for the royal authority, and their concern for borders with the strategies they resort to, which do not make them differ really from their male counterparts.“
Keywords: Königin; Macht; Merowinger (Dynastie); Territorium